The genome sequence of the white ermine, Spilosoma lubricipeda Linnaeus 1758 - Boyes, D; Holland, PWH (F1000Research, 2021)
We present a genome assembly from an individual male Spilosoma lubricipeda (the white ermine; Arthropoda; Insecta; Lepidoptera; Erebidae). The genome sequence is 587 megabases in span. The majority of the assembly is scaffolded into 30 chromosomal pseudomolecules, with the Z sex chromosome assembled.